Exploring intelligent solution for potentially viral municipal solid waste management in China: Research and development of a smart management platform based on the logic of "Requirement-Function-Application" - Li, Ying; Zhang, Sisi; Qu, Yao; Yuan, Ajuan; Chen, Haoxiang (Process safety and environmental protection, 2025)
Informational management of municipal solid waste (MSW) during public health emergencies is crucial for timely prevention of virus carried and transmitted by waste generation source. However, most existing smart technology-based solid waste management measures focus on end-of-pipe treatment. In order to timely and effectively manage the potentially viral municipal solid waste (PVMSW), exploring source control strategies was an urgent need. In this study, two scenarios were proposed based on the realistic scenarios of domestic waste management in closed-loop control areas in China during the epidemic outbreak, namely, the citywide lockdown and control scenario and the citywide dynamic lockdown and control scenario. The requirements of PVMSW source intelligent management were summarized and analyzed under the two scenarios. In this regard, a new idea for MSW source management under public health emergencies was proposed - the PVMSW Smart Management Platform (PVMSW-SMP) with multiple subjects' collaboration. It adopts diversified intelligent technologies fusion method to construct functions around four perspectives of information integration, interactive synergy, real-time supervision and intelligent warning. The structure system consists of four modules: integrated control center, information center, warning center and operation center. The PVMSW-SMP interfaces were designed and developed. In addition, the application feasibility and advantages of PVMSW-SMP were emphasized. The PVMSW-SMP developed in this study helps to realize the PVMSW source informational management in public health emergencies and strengthen the collaborative management of the main subjects of domestic waste epidemic prevention and control. It also provides a feasible solution for the intelligent management of solid waste under similar emergencies. [Display omitted]